Effect of sulfur dioxide on pulmonary vascular structure of hypoxic pulmonary hypertensive rats - Tian, Yue (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2008)
OBJECTIVE: Hypoxic pulmonary hypertension is an important pathophysiologic process of various cardiovascular diseases. Sulfur dioxide (SO2) was considered as a kind of toxic gas previously, but recent studies suggested that SO2 could act as a key bioactive molecule in the pathogenesis of cardiovascular diseases. Therefore, this study was designed to examine the effect of sulfur dioxide on pulmonary vascular structure of hypoxic pulmonary hypertensive rats treated with SO2 donor substances